Estudo de propriedades ópticas de filmes finos de polímeros conjugados ebicamada polimérica - Karolline Aparecida de Souza Araujo (2013)
In this work, we studied optical properties of thin films of poly(nvinylcarbazole) (PVK) and poly(3octadecylthiophene) (PODT) conjugated polymers, as well as a PVK / PODT sequential bilayer deposited on glass substrates. The optical characterization of the samples was done using absorption and photoluminescence techniques. We employed different geometries of collection in the photoluminescence measurements, which were made as a function of temperature, with the samples being cooled inside a liquid He immersion cryostat. Time resolved uorescence technique was also used to characterize the samples. The respective thicknesses and refractive indexes of our thin films were measured by ellipsometry. The PVK emission spectra at different temperatures put in evidence a well-structured red band whose intensity increases with decreasing temperature when the sample is excited by a continuous 375 nm laser line. This red band is assigned to the emission from PVK aggregate states which act as trap states for the monomeric PVK triplet (blue band). At the same low temperatures, these trap states can be avoided when the excitation of the PVK lm is made by a 355 nm pulsed laser line with 10 Hz repetition rate.For the PVK / PODT bilayer we observe a clear competition process between exciton energy transfer (EET) from PVK (donor) to PODT (acceptor), or to its own aggregate states, depending on temperature.